2009
DOI: 10.1002/eat.20714
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic writing as an intervention for symptoms of bulimia nervosa: Effects and mechanism of change

Abstract: For individuals experiencing symptoms of bulimia, the effects of therapeutic writing did not differ significantly from effects of a control writing task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 45 publications
1
41
0
1
Order By: Relevance
“…Whereas increased use of cognitive and insight words typically reflects improvements in health after writing, other studies have also shown this trend but without health benefits at follow-up. 11,32 One study found that this trend was related to improvements in somatic symptoms but not in subjective distress, suggesting only certain types of benefits are derived. 30 Our study demonstrated increasing use of causation words and significantly greater use of cognitive words in the disclosure group but without reduction in eating-disorder symptoms or cognitions, which is consistent with previous findings.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas increased use of cognitive and insight words typically reflects improvements in health after writing, other studies have also shown this trend but without health benefits at follow-up. 11,32 One study found that this trend was related to improvements in somatic symptoms but not in subjective distress, suggesting only certain types of benefits are derived. 30 Our study demonstrated increasing use of causation words and significantly greater use of cognitive words in the disclosure group but without reduction in eating-disorder symptoms or cognitions, which is consistent with previous findings.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…30 Our study demonstrated increasing use of causation words and significantly greater use of cognitive words in the disclosure group but without reduction in eating-disorder symptoms or cognitions, which is consistent with previous findings. 11 We also analyzed how common references to food were in the writings. On the first two days, the control group used significantly more words related to food; however, their use of food words declined significantly overall across the writing task.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
See 3 more Smart Citations